UPAYA PENINGKATAN PERAN BADAN KOMUNIKASI PEMUDA REMAJA MASJID INDONESIA DALAM PROSES LEGALITAS GURU TAMAN PENDIDIKAN ALQUR’AN - , Norma Juainah; Hatta Azzuhri; Saipul Anwar (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
The process of digitizing teacher legality through the Emis website still does not fully cover all teachers so that they are registered in the official data of the Ministry of Religion. This article aims to analyze BKPRMI's contribution to the process of legalizing Al-Quran Teachers and Education Park Units/Al-Quran Kindergartens in Ogan Ilir Regency. The research method applied was qualitative with a case study approach, involving the Ministry of Religion of Ogan Ilir Regency, the BKPRMI DPK management, and three TPA/TKA institutions. Data collection was carried out through interviews and observations. Data analysis was carried out using an interactive model which included three steps: data condensing, data presentation, and drawing conclusions. Research findings indicate that BKPRMI has several functions, such as providing outreach to TPA/TKA regarding the application for IJOP (Operational Permit) and BOP (Educational Operational Assistance) to the Ministry of Religion, as well as organizing training and standardization for TKA-TPA teachers has not been optimal in the legal process for teachers and TKA units. -TPA. Regular and continuous outreach is needed to the sub-districts so that TPA/TKA in Ogan Ilir Regency. BKPRMI's role has been outlined in the work program they carry out. However, with limited facilities, time and resources, the roles they carry out have not been fully carried out effectively.